Molecular Regulation of the CNS by Vitamin D - Máčová, Ludmila; Kancheva, Radmila; Bičíková, Marie (Physiological research, 2023)
Vitamin D is a lipid-soluble vitamin that can be found in some foods. It is also produced endogenously (in the presence of ultraviolet light), transported through the blood to the targets organs and this is the reason to consider vitamin D as a hormone. It is known that vitamin D has genomic and non-genomic effects. This review is focused mainly on the vitamin D receptors, the importance of vitamin D as a neuromodulator, the role of vitamin D in the pathophysiology of devastating neurological disorders such as Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis, Parkinson's disease and the benefit of vitamin D and its derivates in alleviating these disorders.
Keywords: Vitamins; vitaminy; Alzheimerova nemoc; Alzheimer Disease; lidé; Vitamin D; Parkinson Disease; Parkinsonova nemoc; Nervous System Diseases; Humans; nemoci nervového systému; vitamin D